2016
DOI: 10.3390/met6110273
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Behavior of Alumina-Based Inclusions in CaF2-Al2O3-CaO-MgO-SiO2 Slag Used for the Electroslag Metallurgy Process

Abstract: Abstract:Removal of non-metallic inclusions to CaF 2 -based slag is one of the most important functions of electroslag remelting. In this work, the dissolution behavior for alumina-based inclusions in CaF 2 -Al 2 O 3 -CaO-MgO-SiO 2 slag has been investigated. Results indicate that the diffusion or permeability capacity of slag components into alumina particles is F − , Ca 2+ , Si 4+ , Mg 2+ , from strongest to weakest, for CaF 2 -Al 2 O 3 -CaO-MgO-SiO 2 slag. Alumina inclusions react with F − in liquid slag at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…These studies showed that the reaction temperature and slag composition were the dominant factors influencing the dissolution speed of inclusions, while the size and surface roughness of the oxide material could have negative effects on the experimental results. 18,19 Another experimental method for studying inclusion dissolution is applying a high-temperature confocal microscope to observe the dissolution process belonging to a single spherical ball. The dissolution models of an inclusion ball in slag are usually established based on the unreacted shrinking core model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the reaction temperature and slag composition were the dominant factors influencing the dissolution speed of inclusions, while the size and surface roughness of the oxide material could have negative effects on the experimental results. 18,19 Another experimental method for studying inclusion dissolution is applying a high-temperature confocal microscope to observe the dissolution process belonging to a single spherical ball. The dissolution models of an inclusion ball in slag are usually established based on the unreacted shrinking core model.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, a solid oxide bar was usually immersed in molten slag and rotated at different speeds, and then the dissolution speed of inclusions in the molten slag was analyzed by comparing the change in the size of the bar before and after the rotating process. These studies showed that the reaction temperature and slag composition were the dominant factors influencing the dissolution speed of inclusions, while the size and surface roughness of the oxide material could have negative effects on the experimental results 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Chou et al [15] investigated the dissolution of Al 2 O 3 inclusions in the CaO-Al 2 O 3 -CaF 2 system using the rotating cylinder method. Dong et al [16] investigated the dissolution of Al 2 O 3 inclusions in CaF 2 -Al 2 O 3 -CaO-MgO-SiO 2 ESR slag using optical microscopy (OM) and scanning electron microscopy (SEM) analysis of quenched slag. Sridhar's research did not find the formation of intermediate compounds at the alumina/slag interface and found that the dissolution process of alumina is controlled by diffusion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusions are similarly removed through the tundish or using mold flux during casting process, where a quick inclusion dissolution also prevents the early crystallization within the slag that might result in the sticker breakouts. 10,11 Particle dissolution phenomenon in the slags has been traditionally studied using dip-test technique, [12][13][14] whereby a macro oxide bulk material is immersed into a molten slag for a period of time. The dipped oxide material can be static or rotated in the molten slag.…”
Section: Introductionmentioning
confidence: 99%